Longly-attached cap can contribute to en bloc underwater endoscopic mucosal resection of 20–30 mm colorectal intramucosal lesions - Iwagami, Hiroyoshi; Akamatsu, Takuji; Ogino, Shinya; Morimura, Hiroki; Shimoyama, Masayuki; Terashita, Tomoko; Nakano, Shogo; Wakita, Midori; Edagawa, Takeya; Konishi, Takafumi; Nakatani, Yasuki; Yamashita, Yukitaka (Endoscopy International Open, 2022)
Background and study aims Underwater endoscopic mucosal resection (UEMR) is effective for colorectal intramucosal lesions. The aim of this study was to evaluate whether a longly-attached cap in UEMR improves the en bloc resection rate for 20–30 mm lesions.Patients and methods We performed a retrospective study at a tertiary institute. Candidates for the study were systematically retrieved from an endoscopic and pathological database from October 2016 to December 2020. We assessed the procedural outcomes with UEMR for lesions ≥ 20 mm in size and the clinical factors contributing to en bloc resection.Results A total of 52 colorectal lesions that underwent UEMR were included. The median procedure time was 271 (66–1264) seconds. The en bloc resection rate and R0 resection rate were 75 % and 73 %, respectively. Intraprocedural perforation occurred in one (1.9 %) case, but no bleeding occurred. Delayed bleeding occurred in one (1.9%) case, but no delayed perforation occurred. Regarding tumor size, macroscopic type, tumor location, and the presence or absence of a history of abdominal operation, there was no significant difference between the en bloc resection and piecemeal resection groups. The visibility of the whole lesion, a longly-attached cap, and sessile serrated lesions were more frequently observed in the en bloc resection group than in the piecemeal resection group (P < 0.001, P = 0.01, and P = 0.04, respectively). Multivariate analysis showed that a longly-attached cap was the only independent factor associated with en bloc resection (P = 0.02).Conclusions A longly-attached cap might contribute to en bloc resection.